2002
DOI: 10.1001/jama.288.14.1740
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Trajectories of Brain Volume Abnormalities in Children and Adolescents With Attention-Deficit/Hyperactivity Disorder

Abstract: Developmental trajectories for all structures, except caudate, remain roughly parallel for patients and controls during childhood and adolescence, suggesting that genetic and/or early environmental influences on brain development in ADHD are fixed, nonprogressive, and unrelated to stimulant treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

80
970
12
42

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,401 publications
(1,104 citation statements)
references
References 43 publications
80
970
12
42
Order By: Relevance
“…The changes observed in the study controls are in line with findings of longitudinal studies of typically developing children. Similar to longitudinal findings in healthy children and adolescents (Castellanos et al, 2002;Giedd et al, 1999;Lenroot and Giedd, 2006;Rapoport et al, 1999;Sowell et al, 2003), our control group showed an increase in cerebral WM/GM ratio, decrease in caudate volume, and no change in amygdala and hippocampus volumes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The changes observed in the study controls are in line with findings of longitudinal studies of typically developing children. Similar to longitudinal findings in healthy children and adolescents (Castellanos et al, 2002;Giedd et al, 1999;Lenroot and Giedd, 2006;Rapoport et al, 1999;Sowell et al, 2003), our control group showed an increase in cerebral WM/GM ratio, decrease in caudate volume, and no change in amygdala and hippocampus volumes.…”
Section: Discussionsupporting
confidence: 88%
“…Supporting this view, the STG GM reaches it maximal volume later than all other cortical regions after the age of 16 years . The typical caudate development has been observed to increase in childhood and then begins to decrease in size during adolescence (Castellanos et al, 2002). Thus it seems that in 22q11.2DS adolescents pruning of the STG GM and caudate nucleus lags behind that of typically developing adolescents.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, the specificity of our mental rotation fMRI task allows our interpretations to be constrained by known brain-behaviour relationships that exist from nonhuman primate work on spatial working memory. 24,25 The caudate nucleus remains a brain area of significant interest in the pathophysiology of ADHD-CT: decreased caudate nucleus size is a replicated finding in children with ADHD-CT, 43,44 although no difference in size is evident during adolescence. 44 Structural lesion and functional imaging animal data support the association of caudate nucleus dysfunction with core ADHD-CT symptoms, working memory and response inhibition dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 The caudate nucleus remains a brain area of significant interest in the pathophysiology of ADHD-CT: decreased caudate nucleus size is a replicated finding in children with ADHD-CT, 43,44 although no difference in size is evident during adolescence. 44 Structural lesion and functional imaging animal data support the association of caudate nucleus dysfunction with core ADHD-CT symptoms, working memory and response inhibition dysfunction. 1,45 The caudate nucleus has a high concentration of dopaminergic synapses underpinning its functions, dopamine being a key neurotransmitter known to be functionally aberrant in ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Gene association studies have related allelic variants of SNAP25 with attention deficit hyperactivity disorder (ADHD) [Brophy et al, 2002;Mill et al, 2002;Barr et al, 2000]. Although there is no formal evidence supporting a synaptogenesis deficit in ADHD, diminished brain volumes have been reported [Castellanos et al, 2002]. Because of this converging evidence, we investigate the influence of this gene on normal executive attention.…”
Section: Molecular Genetic Studies On Snap25 and Its Potential Role Imentioning
confidence: 97%